Impact of Polyherbal Mixture on Reproductive Traits of Assam Hill Goat - , Chinmoy Dutta, Jyoti Prasad Bordoloi, Raj Jyoti Deka, Naba Jyoti Deka (Archives of Current Research International, 2025)
In this study, 36 Assam Hill goats were chosen and randomly divided into three groups of either sex for comparative analysis of reproductive traits. A mixture of herbal feed was supplemented to the treatment groups @ 1 and 2 grams per kilogram of body weight, starting from 4 months old until they were 12 months old. The mean average age (days) at first heat were 199.833 ± 3.842, 183.333 ± 2.985 and 183.167 ± 4.110 for goats in C0, T1 and T2, respectively. The highest mean semen volume (ml) was found in T2 group at 12th month 0.627 ± 0.008, Similarly, live sperm (%) 85.355 ± 0.895 was found in T2 group at 12th month. The overall semen qualities were found better in T2, followed by T1 and C0. There was improvement in reproductive traits such as age at first heat, heat duration and age at sexual maturity in females as well as semen quality in males.